Pengembangan Media Pembelajaran LKPD Berbasis Predict Observe and Explain untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Perbandingan di Kelas VII SMP (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop learning media in the form of Learner Worksheets (LKPD) based on the Predict, Observe, and Explain (POE) model to overcome students' difficulties in understanding comparison material. The method used is Research and Development (R&D) with stages: identification of potential and problems, data collection, product design, initial trials, design revisions, and product validation. Data collection techniques were carried out through observation, questionnaires, interviews, and tests. Data analysis was done descriptively quantitatively, by calculating the average percentage of validation results, user responses, and test results. The results showed that the POE-based LKPD had a very high level of validity with a score of 87.3%. The practicality of the media is also classified as very good, based on a teacher response questionnaire of 88% and a student response questionnaire of 72%. Meanwhile, the effectiveness of the LKPD is shown through the posttest results with an average score of 79.0%, which meets the effective criteria in improving students' critical thinking skills. Thus, this POE-based LKPD is feasible to use as a valid, practical, and effective learning media on comparison material in grade VII SMP.